Alternative reaction pathways in domino reactions of hydrazinediidozirconium complexes with alkynes: dedicated to Professor Walter Siebert on the occasion of his 75th birthday - Gehrmann, Thorsten; Scholl, Solveig A.; Lloret Fillol, Julio; Wadepohl, Hubert; Gade, Lutz H. (Chemistry - a European journal, 2012)
Reaction of [Zr(NAr)2Npy(NMe2)2] (Ar=3,5-xylyl: 2 a, mesityl: 2 b) with one or two molar equivalents of 1,1-diphenylhydrazine gave the mixed amido/hydrazido(1−) complex [Zr(NMes)2Npy(HNNPh2)(NMe2)] (3), the bis-hydrazido complex [Zr(NMes)2Npy(HNNPh2)2] (4), and, in the presence of excess 4-dimethylaminopyridine (DMAP), hexacoordinate hydrazinediidozirconium complexes [Zr(NXyl)2Npy(NN(Me)Ph)(dmap)2] (5) and [Zr(NXyl)2Npy(NNPh2)(dmap)2] (6). The reaction of one equivalent of the zirconium-hydrazinediide [Zr(NTBS)2Npy(NNPh2)(py)] (1) with disubstituted alkynes at RT for 16 h led to the formation of seven-membered diazazirconacycles 7 a-7 e in high yields. Similar reactivity was observed by reacting bis-amido complex 2 b with one molar equivalent of the corresponding alkyne and diphenylhydrazine. The formation of the seven-membered zirconacycles implied a key coupling step that involved the alkyne and one of the aryl rings of the diphenylhydrazinediido ligand. In some cases, such as the reaction with 2-butyne, the corresponding metallacycle was only obtained in modest yields (45 % for the reaction with 2-butyne) and a second major product, vinylimido complex 9, was formed in almost equal amounts (42 %) by 1,2-amination (formal insertion of the alkyne). The formation of compounds 7 a and 9 followed in part the same sequence of reaction steps and a key intermediate, an azirinido complex, represented a “bifurcation point” in the reaction network. Reaction of 1.2 equivalents of several diarylhydrazines and various substituted alkynes (1 equiv) at ambient temperature (or at 80 °C) in the presence of 10 mol % [Zr(NXyl)2Npy(NMe2)2] (2 a) gave the corresponding indole derivatives. On the other hand, the replacement of 1,1-diarylhydrazines by 1-methyl-1-phenyl hydrazine led to head-to-head cis-1,3-enynes in good yields.
Gesehen am 26.04.2018